A computer method for calculation of the take-off velocity and take-off angle of the center of gravity of a long jumper - Egoyan, A. E.; Gobirakhashvili, A. D. (Національний технічний університет "Харківський політехнічний інститут", 2024)
It is well known that the result of a long jump depends mainly on two parameters: the velocity of the jumper's center of gravity and its angle with horizontal at the take-off moment. This paper presents a new method for the calculation of these parameters from the athlete’s long jump video recording when it is not possible to measure them directly from the video.
Keywords: computer modelling; center of gravity; biomechanical analysis; athletes; комп'ютерне моделювання; спортсмени; стрибки у довжину; біомеханічні аналізи